2023
DOI: 10.1039/d2ra06667j
|View full text |Cite
|
Sign up to set email alerts
|

N,2,6-Trisubstituted 1H-benzimidazole derivatives as a new scaffold of antimicrobial and anticancer agents: design, synthesis, in vitro evaluation, and in silico studies

Abstract: The purpose of this study is to synthesize novel N,2,6-trisubstituted 1H-benzimidazole derivatives and evaluation of their antibacterial, antifungal, and anticancer activities as well as to study their mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…All compounds showed binding in the active site of the enzyme. The 1,2,4-triazole ring of compounds 73a-73l is positioned almost perpendicular to the porphyrin plane, with a ring nitrogen (N-4) atom coordinated to the heme iron (Figure 10) [145,146]. Ahuja et al reported antifungal activity of compounds 74a-74c against F. verticillioides, D. oryzae, C. lunata, and F. fujikuroi (Figure 11).…”
Section: Kankate Et Al Reported the Synthesis Of Hybrids 73a-73l (Sch...mentioning
confidence: 99%
“…All compounds showed binding in the active site of the enzyme. The 1,2,4-triazole ring of compounds 73a-73l is positioned almost perpendicular to the porphyrin plane, with a ring nitrogen (N-4) atom coordinated to the heme iron (Figure 10) [145,146]. Ahuja et al reported antifungal activity of compounds 74a-74c against F. verticillioides, D. oryzae, C. lunata, and F. fujikuroi (Figure 11).…”
Section: Kankate Et Al Reported the Synthesis Of Hybrids 73a-73l (Sch...mentioning
confidence: 99%
“…Cell culture and MTT assay according to our previous protocol. [18] Tumorsphere culture [19] An amount of 1,000 MCF-7 cells cultured in the low-attachment surface plate containing 100 μL of DMEMF12 medium (Gibco-Thermo Fisher Scientific, Waltham, MA, USA) and 20 nM epidermal growth factor and 20 nM fibroblast growth factor, (Sigma Aldrich, St. Louis, MO, USA)). The tumorsphere culture medium was added with 4 c at concentrations of 0, 10 and 40 μM.…”
Section: Representative Procedures For Hydrazide Synthesis Synthesis ...mentioning
confidence: 99%
“… 30 In MCRs, all the reactants are added simultaneously in a one-pot manner that generally results in reducing the cost and time-effective synthesis of the desired products. 31 …”
Section: Introductionmentioning
confidence: 99%